Pathophysiology of Vascular Stenosis and Remodeling in Moyamoya Disease - Fox, Brandon M.; Dorschel, Kirsten B.; Lawton, Michael T.; Wanebo, John E. (Frontiers in Neurology, 2021)
Moyamoya disease (MMD) and moyamoya syndrome (MMS) are progressive vascular pathologies unique to the cerebrovasculature that are important causes of stroke in both children and adults. The natural history of MMD is characterized by primary progressive stenosis of the supraclinoid internal carotid artery, followed by the formation of fragile collateral vascular networks. In MMS, stenosis and collateralization occur in patients with an associated disease or condition. The pathological features of the stenosis associated with MMD include neointimal hyperplasia, disruption of the internal elastic lamina, and medial attenuation, which ultimately lead to progressive decreases in both luminal and external arterial diameter. Several molecular pathways have been implicated in the pathophysiology of stenosis in MMD with functions in cellular proliferation and migration, extracellular matrix remodeling, apoptosis, and vascular inflammation. Importantly, several of these molecular pathways overlap with those known to contribute to diseases of systemic arterial stenosis, such as atherosclerosis and fibromuscular dysplasia (FMD). Despite these possible shared mechanisms of stenosis, the contrast of MMD with other stenotic pathologies highlights the central questions underlying its pathogenesis. These questions include why the stenosis that is associated with MMD occurs in such a specific and limited anatomic location and what process initiates this stenosis. Further investigation of these questions is critical to developing an understanding of MMD that may lead to disease-modifying medical therapies. This review may be of interest to scientists, neurosurgeons, and neurologists involved in both moyamoya research and treatment and provides a review of pathophysiologic processes relevant to diseases of arterial stenosis on a broader scale.